Novel antistatic glass fiber reinforced heat‐resistant PA10T composites with excellent processing properties and thermal stability. Issue 10 (4th January 2023) - Zhu, Rongli; Pu, Zejun; Hou, Hongbo; Wang, Xu; Li, Xianyong; Yu, Dayang; Zhong, Jiachun; Song, Ying
Abstract: In this work, the antistatic effect of antistatic agent (AA) on semi‐aromatic poly (decamethylene terephthalamide) (PA10T) with 30 wt.% glass fiber (GF) was investigated. The PA10T/AGF antistatic composites with excellent thermal characteristics, balanced toughness, and notched impact strength were prepared through one‐step melt blending, and added the AA and GF to the PA10T matrix. Meanwhile, the structure, morphology, thermal properties, and mechanical properties were examined in detail by FT‐IR, SEM, TGA, DSC, and tensile and impulse testing. The results showed that the antistatic GF dispersed well in the PA10T matrix and interacted well with the PA10T matrix. The antistatic properties increased with the increase of AA content, and AA/GF‐5 composites had the best antistatic effect when AA content was 25 wt.%. However, with the increase of AA content, the melt temperature of PA10T/AGF composites decreased, while the machining performance and thermal stability of PA10T/AGF composites increased. The composites' tensile strength and breaking elongation followed a rising and falling pattern with increasing AA concentration. Notwithstanding, the notched impact strength of PA10T/AGF composites decreased and then increased. Therefore, this work provides us with a deep understanding of the antistatic effect of AA on polymers. Abstract : The PA10T/AGF antistatic composites composed of PA10T, antistatic agent, 30 wt.% glass fiber possess excellent antistatic properties, thermal characteristics, balanced toughness, and notched impact strength.